Nationwide surveillance of bacterial respiratory pathogens conducted by the surveillance committee of japanese society of chemotherapy, the japanese association for infectious diseases, and the japanese society for clinical microbiology in 2016: General view of the pathogens’ antibacterial susceptibility - Yanagihara, Katsunori; Matsumoto, Tetsuya; Tokimatsu, Issei; Tsukada, Hiroki; Fujikura, Yuji; Miki, Makoto; Morinaga, Yoshitomo; Sato, Junko; Wakamura, Tomotaro; Kiyota, Hiroshi; Tateda, Kazuhiro; Hanaki, Hideaki; et al. (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2020)
The nationwide surveillance on antimicrobial susceptibility of bacterial respiratory pathogens from the patients in Japan was conducted by the Japanese Society of Chemotherapy, the Japanese Association for Infectious Diseases, and the Japanese Society for Clinical Microbiology in 2016. The isolates were collected from clinical specimens obtained from well-diagnosed adult patients with respiratory tract infections during the period between February 2016 and August 2016 by three societies. Antimicrobial susceptibility testing was conducted at the central reference laboratory according to the method recommended by Clinical Laboratory Standards Institute. Susceptibility testing was evaluated in 1062 strains (143 Staphylococcus aureus, 210 Streptococcus pneumoniae, 17 Streptococcus pyogenes, 248 Haemophilus influenzae, 151 Moraxella catarrhalis, 134 Klebsiella pneumoniae, and 159 Pseudomonas aeruginosa). Ratio of methicillin-resistant S. aureus was 48.3%, and those of penicillin-susceptible S. pneumoniae was 99.5%. Among H. influenzae, 14.1% of them were found to be β-lactamase-producing ampicillin-resistant strains, and 41.1% to be β-lactamase-non-producing ampicillin-resistant strains. Extended spectrum β-lactamase-producing K. pneumoniae and multi-drug resistant P. aeruginosa with metallo β-lactamase were 4.5% and 0.6%, respectively.